Pemahaman Personal Hygiene melalui Pendidikan Kesehatan pada Penghuni Lapas Perempuan Klas II B Yogyakarta - Hadi Pandowo; Chanif Kurniasari (Humanism: Journal of Community Empowerment (HJCE), 2019)
ABSTRACTPhysical, psychological and social needs are basic human needs. These needs cannot be met or disturbed if a person does not or lacks good personal hygiene knowledge and abilities. Personal hygiene is an action to maintain the cleanliness and health of a person for physical and psychological well-being. The purposes of personal hygiene are including increasing the degree of health, maintaining personal hygiene, improving personal hygiene itself, preventing disease, increasing self-confidence, and creating beauty. The understanding and awareness of prisoners in Class II B Women’ Prison in Yogyakarta regarding personal hygiene are still quite low so that several physical and social health problems of prisoners arise. In addition, health education and consultations on personal hygiene have never been provided to prisoners. For this reason, education on Personal Hygiene is needed for prisoners of Class II B Women’ Prison in Yogyakarta. The provision of personal hygiene education received a positive response from the prisoners and officers of Class II B Women’ Prison in Yogyakarta. Keywords: health education, personal hygiene